2007
DOI: 10.1111/j.1365-2222.2007.02748.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on airway inflammation: a cross‐sectional analysis of body mass index and sputum cell counts

Abstract: Summary Background Several observational studies have demonstrated an association between obesity and asthma. Studies evaluating exhaled nitric oxide levels and obesity have revealed that a higher body mass index (BMI) is associated with elevated exhaled nitric oxide levels. Airway inflammation using sputum cell counts has not been assessed in obese patients with airway diseases. Objective The primary aim of this study was to determine whether obesity (based on BMI) is associated with eosinophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
2
9

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 41 publications
6
67
2
9
Order By: Relevance
“…These findings, therefore, suggest a less favorable effect on airway inflammation of ICS in obese patients with asthma. In contrast to the study by Telenga et al [7], an association between obesity and eosinophilic airway inflammation has not been reported from previous studies [8][9][10].…”
contrasting
confidence: 53%
“…These findings, therefore, suggest a less favorable effect on airway inflammation of ICS in obese patients with asthma. In contrast to the study by Telenga et al [7], an association between obesity and eosinophilic airway inflammation has not been reported from previous studies [8][9][10].…”
contrasting
confidence: 53%
“…IL-6 was negatively correlated with FEV1 and FVC (r s 5 -0.376, p,0.001 and r s 5 -0.515, p,0.001, respectively; n5112) and positively with ACQ score (r s 5 0.275, p50.003; n5111). In asthmatic subjects, males had a significantly higher IL-6 (median (IQR) 1.9 (1.3-3.0) versus 1.4 (1.1-2.4) pg?mL -1 ; p50.036), and reduced CRP (2.2 (0.9-5.6) versus 3.5 (1.3-9.6) mg?L -1 ; p50.069) and leptin (3,038 (2,055-5,906) versus 8,205 (3,199) pg?mL -1 ; p,0.001) compared with females.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…Neutrophilic asthma involves innate immune dysfunction, with a persistence of symptoms and airway hyperresponsiveness (AHR) in the absence of sputum eosinophils [5]. Three recent studies reported no relationship between obesity and neutrophilic airway inflammation; however, all showed a clear nonsignificant trend towards increased sputum neutrophils as body mass index (BMI) increased [2][3][4]. The lack of statistical significance in these studies is possibly due to the small sample size in two studies [2,4], sex differences not being considered in two instances [2,3] and the large variation generally observed in the measurement of sputum cell counts.…”
mentioning
confidence: 99%
See 2 more Smart Citations